The Influence of the Problem Based Learning Model And Students' Learning Motivation Towards Physics Learning Outcomes Students of SMAN 5 Takalar - Ridwan, Muhuhammad (Professorline, 2025)
This study investigates the influence of the Problem-Based Learning (PBL) model and students' learning motivation on physics learning outcomes among Grade XII science students at SMAN 5 Takalar. Motivated by low achievement rates under conventional instruction—where only 54.9% of students reached the minimum competency standard—this experimental research involved 70 students divided into two homogenous groups: an experimental class applying PBL and a control class using direct instruction. Data were collected through tests and questionnaires, then analyzed using descriptive statistics, two-way ANOVA, and t-tests. The results showed that students taught with PBL outperformed those in conventional settings, with an average score of 42.06 compared to 31.74. PBL was also effective across both high and low learning motivation levels. However, no significant interaction was found between the learning model and motivation. These findings suggest that PBL can be a consistently effective instructional approach to enhance learning outcomes in physics education, regardless of students’ motivation levels.